“EFFORTS TO DIFFERENTIATE SERVICES AND PRICES ON BUYING INTEREST OF YUDHA AUTO MATIC CAR WASH CONSUMERS IN BANDUNG CITY” - Supratman, Cindy Fatimah; Abidin, Jaenal; Rachmawati, Mariana (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to test and analyze the influence of differentiate services and prices on consumer buying interest in Yudha Auto Matic Car Wash in Bandung. Along with the large number of vehicles in Indonesia, business opportunities in the automotive sector are increasingly wide open. This is used by many companies in developing a car wash service business. All compete for the sake of winning consumer confidence, so that every company needs to create differentiation in order to attract consumer interest and emphasize that the services they offer are the best different from competitors. But before making a decision, consumers tend to evaluate various things based on what they like and not, one of which is price. Because consumers only want to spend a budget according to their abilities. This type of research is descriptive and verificative, research data are primary data and secondary data, data collection techniques through questionnaires, research samples are 100 respondents, the sampling method uses non probability sampling with purposive sampling technique. The variable of this study consists of 1 dependent variable (Y), namely buying interest and 2 independent variables (X), namely service differentiation and price. This research was tested using validity test, reliability test, classic assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test, correlation test, multiple linear regression, hypothesis testing consisting of T test and F test, and coefficient of determination. The results of multiple linear regression tests on buying interest show that service differentiation has an effect of 0.583, and prices have an influence of 0.437, while the simultaneous effect is 0.571. So it can be concluded that service differentiation variables and prices have a significant influence on buying interest.